Ranunculus solhanensis (Ranunculaceae), a new species from eastern Turkey - Si̇nan, Ali̇; Behçet, Lütfi̇; Yapar, Yakup (Phytotaxa, 2021)
Ranunculus solhanensis sp. nov. (Ranunculaceae) is described from Bingöl province (Eastern Anatolia) in Turkey. It is related to R. bulbilliferus and R. munzurensis also distributed in east Anatolia. The new species is easily distinguished from its relatives by morphological features of stem, corolla, stamen and achenes. Achenes and pollen characteristics have been assessed by light microscopy and scanning electron microscopy. Distribution, ecological data and IUCN conservation status of the new species are also provided.